Spring Intermonsoon Future Projection of El Niño and Its Teleconnection at The Maritime Continent During Warmer Period - Mat Zin Muhamad Zuhairi; Salimun Ester; Liew Juneng; Tangang Fredolin (E3S Web of Conferences)
Previous research has mainly concentrated on the effects of climate change, with much less emphasis dedicated on the combined effect of climate change and climate variability. CMIP6 GFDL-ESM4 was chosen as the best General Circulation Model (GCM) in promoting the ability to simulate El Niño and its teleconnection at the Maritime Continent for March-April-May (MAM) after evaluating 32 GCMs from CMIP5/6. In general, CMIP6 was better at simulating El Niño and its teleconnection at the Maritime Continent than CMIP5. The increase in sea surface temperature in the Pacific Ocean, particularly in the Niño 3.4 region, was documented as higher in SSP5-85 than in SSP2-45. Peninsular Malaysia, the southern half of Borneo, and the Philippines will see more dryness as the temperature warms. SSP2-45 during MAM showed more coverage of dryness receiving in the eastern half of Borneo compared to SSP5-85 during the El Niño period. Through the combination of climate change and climate variability influence, SSP5-85 depicted a higher increment of sea surface temperature compared to historical, which could reach about 5 °C positive warmer changes at the centre of the Pacific Ocean region. SSP2-45 and SSP5-85 depicted warmer conditions for precipitation in Peninsular Malaysia and the Northeast part of Borneo.